Multi-decadal tree-ring stable isotope records of apple and pear trees indicate coherent ecophysiological responses to environmental changes in alpine valleys - Singh, Nilendu; Tagliavini, Massimo; Tomelleri, Enrico; Montagnani, Leonardo (Frontiers in Plant Science, 2025)
The ecophysiological and ecohydrological impacts of climate change and progressively increasing atmospheric carbon dioxide (CO2) concentration on agroecosystems are not well understood compared to the forest ecosystems. In this study, we utilized the presence of old apple and pear trees in the alpine valleys of Northern Italy (maintained for cultural heritage purposes) to investigate climate-scale physiological responses. We developed long-term tree-ring stable isotopic records (δ13C and δ18O) from apple (1976-2021) and pear trees (1943-2021). This allowed the reconstruction of key ecophysiological processes like the variations in intrinsic water use efficiency (iWUE), and we investigated how these trees responded to climate and CO2 changes over decades. Results showed a slight declining trend in carbon discrimination (Δ13C) while intercellular CO2 concentration (Ci) for both species has been increasing since the late 1980s. Concurrently both species exhibited a rising trend in iWUE, with apple trees demonstrating higher efficiency, which appears to be primarily driven by the CO2-fertilization effect. The concomitant trends in tree-ring δ18O suggested a relatively stable local hydroclimate during the study period with some species-specific responses. Analyses further revealed that minimum growing season temperature, not precipitation was the most significant factor influencing the rise in iWUE alongside with CO2 fertilization effect. Analyses of species’ δ13C coupled with their respective δ18O confirmed that the rise in iWUE was due to increased carbon assimilation rather than a decline in evapotranspiration. Moreover, coupled δ13C–δ18O analyses suggested increasing trends in carbon assimilation, with apple trees showing higher inter-decadal variations. These long-term records provide a unique opportunity to test and calibrate how these systems respond to recent and anticipated climate change.